Islamic reform and Arab nationalism: expanding the crescent from the Mediterranean to the Indian Ocean (1880s-1930s) - Ghazal, Amal N. (Routledge, 2010)
This book examines the relationship between Islam and nationalism and the evolution of identity politics. Bridging African and Arab histories and giving a cross-national and cross-regional analysis of movements of religious reform, nationalism and anti-colonialism, its wide geographical coverage ranges from Zanzibar on the Indian Ocean through to Oman into the Mediterranean
Don de l'auteure
Keywords: Zanzibar